(untitled) (Global Journal of Science Frontier Research, 2015)
A novel protease producing bacterium was isolated from the natural source. Gram staining & spore staining showed that the organism is gram positive and forms spore during adverse condition in the growth medium. After various tests it was suggested and the features agreed with the description of Bacillus subtilis in Bergey’s Manual of Systematic Bacteriology [20]. It was also identified as B. subtilis with 99.9% identity by API 50 CHB and was also characterized and identified by using a bioinformatics tool PIB (Probabilistic Identification of Bacteria) that suggests the organism was B. subtilis (ID=0.9760).